Mini review: ATP‐dependent proteases in bacteria. Issue 8 (20th May 2016) - Bittner, Lisa‐Marie; Arends, Jan; Narberhaus, Franz
ABSTRACT: AAA + proteases are universal barrel‐like and ATP‐fueled machines preventing the accumulation of aberrant proteins and regulating the proteome according to the cellular demand. They are characterized by two separate operating units, the ATPase and peptidase domains. ATP‐dependent unfolding and translocation of a substrate into the proteolytic chamber is followed by ATP‐independent degradation. This review addresses the structure and function of bacterial AAA + proteases with a focus on the ATP‐driven mechanisms and the coordinated movements in the complex mainly based on the knowledge of ClpXP. We conclude by discussing strategies how novel protease substrates can be trapped by mutated AAA + protease variants. © 2016 Wiley Periodicals, Inc. Biopolymers 105: 505–517, 2016.